The Financial Performace of ESG (Environmental, Social and Governance) Star Listed Companies in Indonesia - Prasadhita, Chandra; Nawawi, Muhammad (Journal of Applied Business, Taxation and Economics Research, 2024)
This study aims to decrypt the financial performance of companies in Star Listed Companies in Indonesia consisting of 8 companies by 2024. Companies that apply ESG principles can improve company performance, because they have innovative and creative resources in carrying out company activities. This research is expected to increase the urgency of companies in Indonesia in paying attention to ESG aspects in their business operations, because it sees that many Indonesian companies are still implementing ESG in order to be attractive to stakeholders and potential investors. Companies must also pay attention to intellectual capital in order to improve company performance to be efficient and effective.